A comparison of the early motor repertoire of very preterm infants and term infants. (May 2021) - Salavati, Sahar; Berghuis, Sietske A.; Bosch, Tess; Hitzert, Marrit M.; Baptist, Dyvonne H.; Mebius, Mirthe J.; Bos, Arend F.
Abstract: Objective: To obtain reference data on the early motor repertoire of very preterm infants compared with healthy term infants at three months' post-term age. Study design: In this observational study, using Prechtl's method on the assessment of the early motor repertoire, we compared the quality of fidgety movements and the concurrent motor optimality score - revised of infants with a gestational age <30 weeks and/or a birth weight <1000 g with healthy infants with a gestational age of 37–42 weeks. Results: One hundred eighty very preterm and 180 healthy term infants participated. The median motor optimality scores - revised of very preterm infants were significantly lower in comparison to those of term infants, with scores of 24 (25th-75th percentiles: 23–26) and 26 (25th-75th percentiles: 26–28), respectively. Fidgety movements were aberrant (abnormal or absent) more often in very preterm infants than in term infants. The odds ratio was 4.59 (95% CI, 1.51–13.92). Compared with term infants, very preterm infants had poorer scores on the subscales age-adequate movement repertoire, observed postural patterns, and movement character with odds ratios ≥2.97. We found no differences regarding observed movement patterns. Conclusion: This study provides reference data on the early motor repertoire of very preterm and healthy term infants. It demonstrates that the early motor repertoire of very preterm infants is poorer than that of term infants, a finding consistent with existing knowledge that prematurity increases the risk of poor neurodevelopment. Highlights: Very preterm infants' early motor repertoires are poorer than those of term infants. Fidgety movements are aberrant more often in very preterm than term infants. This study's early motor repertoire scores can be used as reference data.